2008
DOI: 10.1177/0142723708091043
|View full text |Cite
|
Sign up to set email alerts
|

Deaf and hearing students' referential strategies in writing: What referential cohesion tells us about deaf students' literacy development

Abstract: The ability to organize the referential content of narrative has usually been investigated as a mark of the development of discourse skills. In this study, the pragmatic use of pronominal and nominal forms of reference in written stories was considered instead as a mark of literacy development in deaf and hearing students. Participants in the study were 17 deaf high-school students, 17 school-age matched hearing controls, and 16 hearing second-graders (novice writers) who were asked to write a picture-story, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…Tal fato pode ocorrer, pois o escritor iniciante escreve como se fala, e na fala a contextualização é dada pela interação simultânea entre o emissor e o receptor. Sendo assim, o papel da escrita não está bem estabelecido e pode gerar o risco de ambiguidade pela ausência ou inadequação de Pontuação (Arfé & Perondi, 2008).…”
Section: Discussionunclassified
“…Tal fato pode ocorrer, pois o escritor iniciante escreve como se fala, e na fala a contextualização é dada pela interação simultânea entre o emissor e o receptor. Sendo assim, o papel da escrita não está bem estabelecido e pode gerar o risco de ambiguidade pela ausência ou inadequação de Pontuação (Arfé & Perondi, 2008).…”
Section: Discussionunclassified
“…The study also had the intention to possibly validate a writing assessment instrument for this specific population. However, the sample size limitation, also observed in other studies with deaf subjects (13,14) , and the number of studied variables prevented this standardization.…”
Section: Introductionmentioning
confidence: 98%
“…With that in mind, a study (13) has suggested that the focus of investigation regarding the production of deaf individuals is changed to the analysis of Communicative Competences, which has demonstrated that the difficulties of these subjects are not that different from their hearing peers. The ability to referentially organize the content of narration has been investigated as a mark of the development of competences in the discourse of these individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing-impaired children's reading and writing skills have been investigated extensively in the school-aged population, consistently revealing low levels of proficiency (Alamargot, Lambert, Thebault, & Dansac, 2006;Antia et al, 2005;Arfé, 2003;Arfé & Boscolo, 2006;Arfé & Perondi, 2008;Banks, Gray, & Fyfe, 1990;Dyer, MacSweeney, Szczerbinski, Green, & Campbell, 2003;Fabbretti, Volterra, & Pontecorvo, 1998;Singleton, Morgan, DiGello, Wiles, & Rivers, 2004;Wauters, van Bon, & Tellings, 2006). However, by comparison, fewer studies have focused on hearing-impaired children's emergent literacy skills or on their early exploration and discovery of the writing system (see Williams, 2004).…”
Section: Introductionmentioning
confidence: 99%